ANTECEDENT KINERJA MANAJERIAL - Chomsatu, Yuli (PARADIGMA, 2014)
This study aims to examine the antecedent variables of managerial performance. As for the antecedent variable in this studi are the variables of leadership style and budget participation. Object of this study is middle- managers in Function Finance / Accounting / Budgeting / Budget that works on Ministry in Boyolali . Respondent in this research employees biro of finance, budgeting, planning in the ministry. The results of this study indicate that leadership style influence on managerial performance . While the budget participation not affect the managerial performance . Then the next result shows that the leadership style and budgetary participation jointly affect managerial performance .Keywords : leadership,budgetary participation , managerial performance